A stratospheric mission – design of a conceptual framework to bring weather balloons and STEM into the classroom - Connolly, Cornelia; Johnson, Patrick; Johnson, Kevin; Fitzpatrick, Mary; O’Keeffe, Derek T. (Frontiers in Education, 2023)
Integrated STEM education makes learning relevant and applicable, blending the mindset, skillset, and toolset necessary in developing a depth of understanding for science, technology, engineering and mathematics. Based on the theoretical framework of Kelley and Knowles (2016) the 'Spaceship Earth' project was designed to engage primary school children in 4 th class (ages 9 and 10 years old) in real-world project-based experiments in the classroom that are used to develop collaborative problem-solving skills and a framework for asking and answering scientific questions. This project involved researchers from two Universities and the Irish National Meteorological Service working collaboratively on a high-altitude balloon mission. High-altitude balloons have an established track record of safe and effective use in weather forecasting, astronomy, and STEM outreach. During the project lifecycle the children devised experiments that they launched to the stratosphere using the high-altitude balloons. Once the experiments returned to Earth, the children engaged in analysis and discussion about their experiments that extended and deepened their learning. This celestial project framework represents a new dawn of innovation for STEM education and public engagement.